Characterising Rht-A1b for the generation of novel semi-dwarfing alleles in wheat - Rafter, Megan (2020)
The dramatic wheat yield increases of the Green Revolution are partially attributed to the development of high yielding, lodging resistant, semi-dwarf varieties through the introduction of the alleles Rht-B1b and Rht-D1b into elite wheat cultivars. These alleles contain gain-of-function mutations in the RHT-1 genes, encoding DELLA proteins that repress gibberellin (GA) signalling. GAs promote the targeted degradation of DELLAs, relieving their repression and allowing for GA-responsive growth. Rht-1 dwarfing alleles encode abnormal DELLA proteins that are not believed to be recognized for degradation, causing constitutive repression of GA responses and pleiotropic effects such as: reduced fertility during heat stress and impaired seedling emergence and establishment. Currently, this limits the ability of Rht-1 alleles for further improving wheat grain yields. The hexaploid bread wheat genome contains three homoeologous Rht-1 genes; RhtA1/B1/D1, although presently dwarfing alleles have only been identified in Rht-B1 and D1. This thesis describes the characterization of the novel allele Rht-A1b through phenotyping, GA-dose response assays, hormononics and transcriptomics analyses. Studies confirmed that Rht-A1b is the first reported Rht-A1 allele that causes GAinsensitive dwarfism and represents a potential tool for wheat breeders. To extend the collection of Rht-A1 dwarfing alleles available to wheat breeders suppressor screens was conducted on M2 ethyl methanesulfonate mutagenised RhtA1b populations. Intragenic Rht-A1b mutants were identified in the field and the BC2F3 generation characterized in the field and glasshouse. All intragenic alleles were found to rescue plant height in comparison to Rht-A1b with six alleles demonstrating a potentially beneficial intermediate phenotype. Testing following an introduction into elite germplasm could establish their potential as superior dwarfing alleles and provided insights into DELLA structure-function in wheat. In addition, a reverse genetics-based approach, TILLING, was used to generate Rht-1 knock out lines, which were subsequently stacked. The triple mutant produced the first identified GA overdose phenotype in wheat, suggesting that DELLA is the negative regulator of GA in wheat. Limited phenotypic differences between combinatorial mutants suggests that there is limited homoeologue specificity in the Rht-1 genes.